ACCOUNTING TREATMENT AND REPORTING FOR FIXED ASSETS IN MILITARY INSTITUTIONS (A CASE STUDY IN DIRECTORATE OF ARMY ENGINEERS? - Indarani Setyaputri (Jurnal Ilmiah Mahasiswa FEB, 2018)
In implementing accounting in the public sector there are many governments that can beclassified in the public sector, one of which is in the Military Institution. The Military Institutionactually also issued the same basis in financial reporting and its accounting with other publicsectors. Fixed assets in the Military Institution are slightly different from other governmentinstitutions related to military assets that are used and prepared by the government that are usedto train members of the army and prepare movements against separatist movements in Indonesiathat produce weapons, buildings and transportation equipment. Public information disclosurethrough Law number 14 of 2008 concerning further disclosure of information about submittinginformation on assets to military assets related to related information distributed by parties notresponsible for requests for military assistance needed by Indonesia. The object of research is theinfluence of Government Regulation No. 16 of 2010 concerning the implementation of Lawnumber 14 of 2008 concerning complaints of public information on fixed assets related to themilitary at the Directorate of Army Engineering considering the presentation of relevant financialstatements that can be carried out by Law. Regarding public information disclosure wherereports can be given if there are no secrets and can be protected by national security. Keywords: Fixed Assets, Military Assets, Disclosure of Public Information.